Could the Inflation Reduction Act Maximum Fair Price Hurt Patients? - Anne M. Sydor; Esteban Rivera; Robert Popovian (Journal of Health Economics and Outcomes Research)
# Background The Inflation Reduction Act’s Medicare Drug Price Negotiation Program allows the federal government to negotiate caps for select medications. These price caps may reduce revenue for the pharmacy benefit managers (PBMs) that negotiate the actual price paid for medicines in the U.S. To offset the resulting pressure on their profit margins, it is possible that PBMs would, in turn, increase patients’ out-of-pocket costs for medicines with capped prices. The model presented here evaluates how increased out-of-pocket costs for the anticoagulants apixaban (Eliquis) and rivaroxaban (Xarelto) could impact patients financially and clinically.